TRAINING FOR GRADE I AND II ELEMENTARY SCHOOL CHILDREN TO UTILIZE THE TRADITIONAL GAME DARET DAMAR JAN AS A MEDIUM FOR LEARNING MATHEMATICS - Labuem, Susana (LPPM Institut Pendidikan Nusantara Global, 2024)
This Community Service activity (PKM) aims to train elementary school students in grades I and II in Dokabarat village to perform natural number counting operations by utilizing damar fruit through traditional games as learning media. The result of this PKM activity is that elementary school students in grades I and II in Dokabarat village can more easily understand the concept and perform natural number counting operations by utilizing the traditional game of daret damar jan as a learning medium.This Community Service Activity (PKM) aims to train elementary school students in grades I and II in Dokabarat village to perform natural number counting operations by utilizing buah damar jan through traditional games as a learning medium. The results of this PKM activity are that elementary school students in grades I and II in Dokabarat village can more easily understand the concept and perform natural number counting operations by utilizing the traditional game of daret damar jan as a learning medium.